Inventario Florístico (arboreo) en el Bosque Siempreverde Montano de la Cordillera occidental de Los Andes en el sector La Esperanza, Parroquia El Tingo, cantón Pujilí Provincia de Cotopaxi a los 2000 msnm. - Chaluisa Chaluisa, Myrian Alicia (2017)
The present research work reflects the current state of the floristic composition of the native forest of La Esperanza and provides data related to the density, abundance, dominance and use value of the identified species. Where 21 species were sampled with a total of 172 trees found in the place among which the 3 families; Euphorbiaceae: Sapium sp (caucho), Symploccaceae: Syaploccos sp (motilón blanco) y Lauraceae: Benthamiana sp (canelo) Finally, with the information obtained a botany guide was elaborated where 21 individuals were identified, each individual has his / her respective photos and information